A philosophical reflection on the nature and relevance of Azikiwe’s political ideology of neo-welfarism - Paul T Haaga; Michael Sunday Sasa (International Journal of Humanities and Innovation (IJHI), 2019)
This paper attempts a reflection on the nature and relevance of Azikiwe’s Political philosophy of Neo-Welfarism. Azikiwe advanced Neo-welfarism as a political ideology as his contribution to the search for ideology in the aftermath of colonialism. With Neo-Welfarism, Azikiwe sought to advance a philosophy for colonial emancipation and the decolonization of Africa. At the background of this ideology is his dissatisfaction with the dominant ideologies of the era being capitalism, socialism and welfarism. This dissatisfaction triggered an attempt to formulate a via media that takes into cognizance, the 'good' aspects of these ideologies through the method of eclectic pragmatism for the greatest good of the greatest number. This paper found out that one of the main objectives of Neo-welfarism is to build a system that works to the advantage of many rather than one that speculates and works to the disadvantages of many. This paper also found out that Neo-welfarism as a political ideology is not without flaws; this is because the workability of such a via media has been called to question among other issues that are at the kernel of this ideology. The conclusion that is reached in this paper is in two folds: one, the articulation of neo-welfarism when there was an apparent search for ideology for the decolonization of Africa is both timely and laudable. Two, the non-mplementation of neo-welfarism after several decades of its advancement; notwithstanding, it is yet relevant in the sustained need to deepen democracy and search for an operational ideology for African's development even today.